Wild edible plants: Nutritional and toxicological characteristics, retrieval strategies and importance for today's society - Pinela, José (2018)
Wild edible plants (WEPs) are part of the cultural and genetic heritage of different regions of the world. In times of famine and scarcity, these sources of nutrients and health-promoting compounds have received high importance mainly in rural and suburban areas. Although currently underutilized, WEPs are still consumed traditionally by different communities and are gaining relevance in today's society. However, these foods lack recognition as significant contributors to the human diet in developed areas. This review describes the nutritional value of WEPs from the North-eastern region of Portugal and points out those containing potentially toxic compounds. Several retrieval strategies are presented with the aim of promoting the (re)use, production, commercialization and conservation of WEPs (wild harvested plants and crop wild relatives), and their importance for social, economic and agro-ecological development is highlighted.